Innate Sensing of the Gut Microbiota: Modulation of Inflammatory and Autoimmune Diseases - Ignacio, Aline; Morales, Camila Ideli; Câmara, Niels Olsen Saraiva; Almeida, Rafael Ribeiro (Frontiers in Immunology, 2016)
The mammalian gastrointestinal tract harbors a diverse microbial community with which dynamic interactions have been established over millennia of coevolution. Commensal bacteria and their products are sensed by innate receptors expressed in gut epithelia and in gut-associated immune cells, thereby promoting the proper development of mucosal immune system and host homeostasis. Many studies have demonstrated that host–microbiota interactions play a key role during local and systemic immunity. Therefore, this review will focus on how innate sensing of the gut microbiota and their metabolites through inflammasome and toll-like receptors impact the modulation of a distinct set of inflammatory and autoimmune diseases. We believe that a better understanding of the fine-tuning that governs host–microbiota interactions will further improve common prophylactic and therapeutic applications.